Third Five Year Plan Second Year's Progress Report (1962-63) Government of Kerala - Planning Commission (Planning Commission, 1962)
The outlay for State Plan schemes under “Agricultural Production” for 1962-63 was Rs. 170.367 lakhs and for Centrally Sponsored schemes, Rs. 2.425 lakhs. In addition to the above, there was a provision of Rs. 1.370 lakhs for the schemes sponsored by the Indian Council of Agricultural Research and another provision of Rs. 0.258 lakh for the scheme ‘‘Manurials Trials for coconut development” sponsored by the Indian Central Coconut Committee. During the course of the year, it was decided to limit the expenditure on State Plan Schemes to Rs. 120.33 lakhs and on I. C. A. R. Schemes to Rs. 0.61 lakh.
Government of Kerala, Planning Department